Transport priority for infrastructure vs. services. IN Policy Note [column] BBB and urban transport policy - Ocampo, Romeo B. (2019)
The Build, Build, Build (BBB) Program was launched by the Duterte administration in 2017 as its strategy to hasten economic growth and deal with transport problems, including the critical traffic congestion in Metro Manila. Implementing BBB, however, may be easier ordered than done. This policy note tries to show how BBB is part of the legacy of historical
and present-day partiality to road-building. Caution is particularly called for in using road infrastructure, which have been hobbled by various constraints, which have been hobbled by various constraints, which have been hobbled by various constraints, as the leading solution to traffic congestion and other transport problems in large urban areas. The challenges in transport planning and design are much more formidable, as indicated by the shortcomings of past plans and projects against the problems. The roadbuilding solution to traffic congestion is short-lived in effectiveness due to induced travel demand. Studies abroad show that this is a complex phenomenon in which land development along road
improvements influence traffic and deserve systematic attention. Such studies should also be undertaken in our metropolitan areas to ascertain whether and to what extent the findings abroad apply to our context. The article concludes with suggestions for attending to some unfinished business in urban transport policy, planning, and administration. It ends with parting notes on the study of public services and Public Administration.
Keywords: Build, Build, Build (BBB) Program; Transportation policy; Infrastructure (Economics) -- Government policy; Urban transportation -- Socio-economic aspects; Transportation industry